PENGARUH STRUKTUR MODAL DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Oktaviani Suarjaya; Suryanto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Abstract: Companies certainly have a way to face competitors in the business world. Company value is something that must be considered and maximized to fight competitors and achieve the goals of the company. The purpose of this research is to obtain empirical evidence about the effect of capital structure, institutional ownership, managerial ownership, profitability, liquidity, dividend policy, company size, and company growth in firm value. The population used in this research are non-financial companies listed on the Indonesia Stock Exchange from 2019-2021. The sample used in this research was based on the sample-on-sample criteria using the purposive sampling method, namely 61 companies that 183 data were obtained as samples. The research method used in analyzing the data is the multiple regression method. The result of this study indicates that capital structure and profitability have a positive effect on firm value, and company growth has a negative effect on the company. Institutional ownership, managerial ownership, liquidity, dividend policy, and company size have no effect on firm value. Keywords: Firm Value, Capital Structure, Institutional Ownership, Managerial Ownership, Profitability, Liquidity, Dividend Policy, Company Size, and Company Growth.